ANTIOXIDANT AND HYPOGLYCEMIC EFFECTS OF WATERCRESS (NASTURTIUM OFFICINALE) EXTRACTS IN DIABETIC RATS - Fenton-Navarro, B.; Martínez, MV. Urquiza; Castro, BB. Fiscal; Castillo, OI. Medrano; López-Rodríguez, M.; Padilla Arellanes, S.; Vázquez Hernández, A. (African Journal of Traditional, Complementary and Alternative Medicines, 2018)
Background: Watercress is a semi-aquatic plant used in traditional medicine to treat various ailments, such as flu, cough, avitaminosis, and anorexia; it is also used as a diuretic and for hypoglycemia treatment in diabetes. In this study, we report the antioxidant and hypoglycemic activity of orally administered aqueous (WAQE), acetonic (WAE), and alcoholic (WOHE) watercress extracts. The effect of subchronic administration of watercress extracts on oxidative stress was also studied. Materials and Methods: WAQE, WAE, and WOHE were obtained and administered orally. Alloxan (200 mg/kg) and streptozotocin (60 mg/kg) were applied to induce hyperglycemia in male Wistar rats. Phenolic and flavonoid content, as well as antioxidant activity of the extracts were measured. The acute and subchronic effects (8 weeks) of WAQE were evaluated. The activity of antioxidant enzymes levels of malondialdehyde, hepatic enzyme markers in the serum, and renal function markers, were assessed. Histopathological evaluation of the pancreas, kidney, and liver was performed using hematoxylin-eosin staining. Results: Watercress extracts have high concentrations of phenols, polyphenols, and flavonoids, in addition to a very high antioxidant effect. The hypoglycemic effect of WAQE upon acute administration was 76.6% higher than that of insulin. When administered chronically, glucose levels were normalized on the third week up to the eighth week. Furthermore, the antioxidant enzymes and biochemical parameters improved. Conclusion: WAQE administration to diabetic rats reduced oxidative stress damage and decreased glucose levels. This study supports the use of this plant for the treatment of diabetes.